2013
DOI: 10.2147/cia.s49644
|View full text |Cite
|
Sign up to set email alerts
|

Impact of beta2-agonists, beta-blockers, and their combination on cardiac function in elderly male patients with chronic obstructive pulmonary disease

Abstract: PurposeThis study was undertaken to determine the association between cardiac function and therapy with beta2-adrenoceptor agonists (β2-agonists), β-blockers, or β-blocker–β-agonist combination therapy in elderly male patients with chronic obstructive pulmonary disease (COPD).Patients and methodsThis was a retrospective cohort study of 220 elderly male COPD patients (mean age 84.1 ± 6.9 years). The patients were divided into four groups on the basis of the use of β-blockers and β2-agonists. N-terminal fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
7
0
3
Order By: Relevance
“…However, NT-proBNP >500 pg/ml predicted one year mortality in 144 patients with predominantly mild to moderate COPD and preserved LVEF (>40%) undergoing major vascular surgery (adjusted HR 7.7 [95% 1.6–37.4]) [49]. NT-proBNP was also associated with all-cause mortality in a larger cohort of 220 elderly men with COPD (adjusted HR 1.61 [1.27–2.06]), although 26% of that cohort had documented HF [50]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NT-proBNP >500 pg/ml predicted one year mortality in 144 patients with predominantly mild to moderate COPD and preserved LVEF (>40%) undergoing major vascular surgery (adjusted HR 7.7 [95% 1.6–37.4]) [49]. NT-proBNP was also associated with all-cause mortality in a larger cohort of 220 elderly men with COPD (adjusted HR 1.61 [1.27–2.06]), although 26% of that cohort had documented HF [50]. …”
Section: Resultsmentioning
confidence: 99%
“…NT-proBNP was also associated with all-cause mortality in a larger cohort of 220 elderly men with COPD (adjusted HR 1.61 [1.27–2.06]), although 26% of that cohort had documented HF [50]. …”
Section: Resultsmentioning
confidence: 99%
“…We included 23 observational studies and 14 RCTs that reported on patients with COPD, in the systematic literature review. Out of a total of 23 observational studies, 21 reported on mortality [ 24 44 ], five reported on AECOPD [ 24 , 33 , 35 , 45 , 46 ] three reported on all-cause hospitalization [ 47 49 ], one reported on SGRQ [ 45 ] and one reported on SF-36 [ 42 ]. From a total of 14 RCTs, 12 reported on FEV1 [ 50 61 ], two each reported on 12MWT [ 59 , 62 ] and 6MWT [ 12 , 56 ] and two reported on SGRQ [ 12 , 56 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There were 21 observational studies reporting on mortality [ 24 , 25 , 27 41 , 43 , 44 , 64 ] which evaluated the effect of beta-blockers vs. no beta-blocker use, in an overall population of 422,552 patients from at least 11 countries (Additional file 1 : Table S2). According to inclusion criteria, 15 studies enrolled patients with COPD and a CVD indication [ 25 , 27 29 , 34 , 37 , 39 , 40 , 43 , 64 , 65 ], while the remaining six [ 24 , 26 , 32 , 33 , 35 , 44 ] did not specify whether those with CVD were specifically excluded; however, all studies had varying percentages of CVD comorbidities. Overall, patient characteristics varied: mean age ranged between 62.8 [ 24 ] and 84.6 [ 44 ] years old and the proportion of males between and 37% [ 26 ] and 100 [ 44 ]%.…”
Section: Resultsmentioning
confidence: 99%
“…У пациентов с ХОБЛ в 2-3 раза выше риск развития ССЗ [7]. АГ и ХОБЛ -одно из частых коморбидных состояний, сочетание этих заболеваний определяет высокий уровень инвалидности и неблагоприятный прогноз [9][10][11][12]. Частота АГ у больных с ХОБЛ варьирует от 6,8 до 76,3%, составляя в среднем 34,3%, что зависит от исследуемого контингента больных и методов диагностики заболеваний органов дыхания (спирометрия, рентгенография органов грудной клетки и др.)…”
unclassified